2022
DOI: 10.3390/ijerph19042454
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Scoping Review of Pre-School Self-Regulation Interventions from a Self-Determination Theory Perspective

Abstract: Self-regulation (SR) is considered foundational in early life, with robust evidence demonstrating a link between early self-regulation and longer-term outcomes. This has been the impetus for a growing body of intervention research into how best to support early SR development, yet approaches and effects are diverse, which complicates an understanding of the critical characteristics for effective early SR intervention. Using Self-Determination Theory (SDT) as a guiding framework, we present a scoping review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Saugy et al 28 reviewed research in physical education with a self‐determination framework, and Szabo and Juwono 29 reviewed the efficacy of SDT‐based interventions in increasing students' physical activity, and both reviews suggest that SDT‐based interventions have the potential to increase physical activity. A review of pre‐school self‐regulation interventions from an SDT perspective found that targeting competence and nurturing children's autonomy led to more effective interventions, whereas relatedness appeared to have less impact 30 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Saugy et al 28 reviewed research in physical education with a self‐determination framework, and Szabo and Juwono 29 reviewed the efficacy of SDT‐based interventions in increasing students' physical activity, and both reviews suggest that SDT‐based interventions have the potential to increase physical activity. A review of pre‐school self‐regulation interventions from an SDT perspective found that targeting competence and nurturing children's autonomy led to more effective interventions, whereas relatedness appeared to have less impact 30 …”
Section: Resultsmentioning
confidence: 99%
“…We found 11 recent reviews of the use of SDT in health contexts, 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 which we summarize briefly below, starting with more general reviews of health behaviour change, and moving to reviews that have a more specific context, including those that have focused on particular medical conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second limitation of the extant research evaluating at‐scale public preschool programs is a near‐exclusive focus on academic outcomes, ignoring EF (for exceptions, see Ansari et al, 2020; Weiland & Yoshikawa, 2013). Evidence from evaluations of specialized curricula or interventions focused on improving EF in preschool contexts suggests preschool may improve children's EF skills at the end of the preschool year (e.g., Bierman et al, 2008; Day et al, 2022; Diamond et al, 2007; Howard et al, 2020; Raver et al, 2008). Given that EF skills have long been considered “cornerstones of development” because they facilitate success in other domains (Robson et al, 2020; Shonkoff & Phillips, 2000; Spiegel et al, 2021), it is important to consider whether, for how long, and to what extent there may be impacts of more typical preschool attendance on EF that continue during and beyond kindergarten.…”
Section: Prior Research Estimating Preschool Benefitsmentioning
confidence: 99%
“…In this respect, learner self-regulatory processes are important. Self-regulation concerns the process of learners regulating motivational, affective, cognitive and social contextual learning aspects (Day et al , 2022; Pintrich, 2004; Zimmerman, 1990). Self-regulatory processes for teacher-directed learning may include the learner skills of acting meekly, accepting instruction, collecting and organizing information, understanding information as intended by the instructor and remembering the information.…”
Section: Teacher-directed Learning and Creativitymentioning
confidence: 99%